The Economic of Employee Benefits - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1971)
This paper explores some of the factors determining the relative magnitude of select wage supplements. While the first section provides some insights into the nature and magnitude of all wage supplements in Canadian industries, subsequent sections are limited to the analysis of private employee benefit plans, their determinants and of their determining factors.